Distribution of Neoperla (Plecoptera: Perlidae) in North Carolina, with new state records for three species - Lenat, David R. (Illiesia, 2009)
Three new state records of Neoperla were collected as adults, N. catharae, N. coosa, and N. stewarti. Mapping of nymphal data (at the genus level) indicatedthat Neoperla occurs throughout most of the state, but it is absent from the mountains and the northern upper coastal plain. Neoperla occurs mainly in smaller streams in the western Piedmont ecoregion, but occurs mainlyin rivers in the eastern part of the state. Up to three species were found to coexist at some sites.
Keywords: entomology; Perlidae; distribution; entomologija; Plecoptera; vrbnice; Neoperla; Nort Carolina; USA